Stochastic security‐constrained hydrothermal unit commitment considering uncertainty of load forecast, inflows to reservoirs and unavailability of units by a new hybrid decomposition strategy. Issue 12 (1st December 2014) - Ansari, Mohammad Reza; Amjady, Nima; Vatani, Behdad
Abstract : This study presents a new stochastic security‐constrained hydrothermal unit commitment (SSCHTUC) model considering the uncertainty of load forecast, prediction of inflows to hydro reservoirs and unavailability of units. In addition, the proposed SSCHTUC includes AC network modelling. To cope with the large‐scale and mixed‐integer non‐linear nature of the model, a new hybrid decomposition strategy composed of generalised Benders decomposition and outer approximation/equality relaxation (OA/ER) is proposed. In addition, to handle the uncertainty sources, a combination of scenario approach and two‐stage stochastic programming is suggested. The proposed SSCHTUC model and decomposition strategy are tested on the IEEE 9‐bus and 118‐bus test systems. Obtained results illustrate the effectiveness of the developed approach.